Pemanfaatan SPADA Berbasis Budaya Lokal dalam Penguatan Kemampuan Listening Mahasiswa pada Mata Kuliah Intermediate Listening: The Use of Local Culture-Based SPADA to Strengthen Students’ Listening Skills in the Intermediate Listening Course - Asna Wirayanti; M. Hafiz Sukri; Waode Sitti Wardani; Andi Muh. Ruum Sya'baan (PT. CASA CENDEKIA MEDIA, 2026)
The use of digital technology in English language learning should be designed contextually so that it supports both academic competence and cultural understanding. This study aims to describe the implementation of a local culture-based Online Learning System (SPADA) in strengthening students’ listening skills in the Intermediate Listening course. The study used a descriptive approach involving students enrolled in the course as participants. Learning activities were conducted by integrating English audio and audiovisual materials containing local folklore, traditions, social environments, and cultural practices into the SPADA platform. Data were collected through listening tests, classroom observations, student response questionnaires, and documentation. The results show that local culture-based SPADA helped students understand vocabulary, identify general and specific information, determine main ideas, and interpret meanings in listening texts. Familiar cultural contexts also increased students’ participation, motivation, and engagement. The study implies that local culture-based SPADA can function as a contextual, flexible, and relevant digital medium for listening instruction.